PEMBUATAN SISTEM PENGUKURAN DURASI PENYINARAN MATAHARI BERBASIS MIKROKONTROLER ATMEGA8535 MENGGUNAKAN SENSOR LDR - Ridho Pratama (Department of Physics – Universitas Negeri Padang UNP, 2013)
Abstact-The purpose of this reseach was to make measurement system of the sunshine duration based on microcontroller ATMEGA8535 which used LDR sensor. This system was expected to measure light intensity and sunshine duration with good performance and design specifications. The collection of data was done directly and indirectly measurement. Direct measurements were done to get output voltage, light intensity and sunshine duration. Indirect measurements were done to get accuracy and precision of system. Performance specifications of this system were built by power supply, LDR sensor, voltage divider circuit, microcontroller ATMEGA8535, and LCD. While design specification consist of five result. First, output voltage was logaritmic of light intensity. Second, on the first day there were three intervals duration of sunshine with a total sunshine duration was 184 minutes, while on the second day there were three interval duration of sunshine with a total sunshine duration was 440 minutes. Third, the accuracy measuring of the light intensities was 97.145%. Fourth, the precision measuring of the light intensities was 0.965. Fifth, the accuration measuring of the sunshine duration was 93.64%. Keyword: System, Sensor, LDR, Sunshine Duration, Microcontroller